2019
DOI: 10.11646/zootaxa.4585.2.1
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the identities of the elasmobranch fauna of Sri Lanka

Abstract: Identities of elasmobranchs from Sri Lanka encountered during collections conducted in an intensive nine-day survey of fish markets and landing sites at 11 localities in the North Western, Northern, and Eastern Provinces in March of 2018 were assessed. In total, 111 specimens representing 34 elasmobranch species were examined. Sequence data for the NADH2 gene were generated for all specimens. Independent Neighbor-Joining analyses, which included data for related taxa, were conducted for 25 subgroups of elasmob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 28 publications
(56 reference statements)
4
25
0
1
Order By: Relevance
“…The body cavity of each shark was then opened with a mid-ventral incision, and a small sample of liver tissue was removed and preserved in 95% ethanol for molecular verification of host identities. Sequence data generated for the protein-coding gene NADH dehydrogenase subunit 2 (NADH2) for six of these seven specimens by Fernando et al (2019) confirmed the novelty of this shark species which, following these authors, we refer to here as Chiloscyllium sp. 1.…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…The body cavity of each shark was then opened with a mid-ventral incision, and a small sample of liver tissue was removed and preserved in 95% ethanol for molecular verification of host identities. Sequence data generated for the protein-coding gene NADH dehydrogenase subunit 2 (NADH2) for six of these seven specimens by Fernando et al (2019) confirmed the novelty of this shark species which, following these authors, we refer to here as Chiloscyllium sp. 1.…”
Section: Methodssupporting
confidence: 74%
“…A series of digital photographs was taken and basic morphometric data were gathered for each specimen. Detailed data for individual sharks are available in the Global Cestode Database (elasmobranchs.tapewormdb.uconn.edu) (Caira et al 2019) using the collection code and number. The body cavity of each shark was then opened with a mid-ventral incision, and a small sample of liver tissue was removed and preserved in 95% ethanol for molecular verification of host identities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Arabic whipray, M. arabica, was first described from specimens collected in coastal habitats of the northern Indian Ocean, off India and Pakistan, by Manjaji-Matsumoto and Last (2016). The Arabic whipray was also recorded from Sri Lanka (Fernando et al 2019). This study described M. arabica as a new distributional record from the Persian Gulf off Iraq.…”
Section: Introductionmentioning
confidence: 99%